A missão jesuítica em movimento na américa portuguesa: do estabelecimento ao plano civilizador (1549-1558) - Oliveira Júnior, Antônio Santos De (2021)
This work (OLIVEIRA JUNIOR, A. S. de. A missão jesuítica em movimento na América portuguesa: do estabelecimento ao Plano Civilizador (1549-1558). 2021. 173 f. Dissertação (Mestrado em Educação) - Universidade Federal de Alfenas, Alfenas, MG, 2021.) observed the establishment and transformations of the Jesuit mission in Portuguese America between the years 1549 and 1558. To carry out the research, letters produced by Father Manuel da Nóbrega, leader of the mission in Portuguese America during the proposed period, and José de Anchieta, one of the main names in the establishment of the missionary project, were taken as sources. In addition to the analyzed letters, the research made use of a specialized bibliographic base, which ensured the interpretative guidance of the colonial context in the 16th century. We tried to analyze the Jesuit missionary project taking into account the multiple factors that influenced and were present in the reports of the priests in question. To guarantee the fulfillment of our objective, we will delimit the formative aspects present in the formation of the Jesuits who went to Portuguese America, so that we can then observe how the Jesuits mobilized this framework to establish the foundations of the mission. Having these elements exposed, we focus on the pedagogical strategies adopted by the priests to convert the indigenous people, identifying the obstacles, the new perceptions about the natives and the strategic redirections made during the period. Having gathered this information, we analyzed Manuel da Nóbrega's mobilization in defense of the maintenance of the mission in Portuguese America and his proposal for the reconfiguration of the Jesuit mission announced in the “civilizing plan” in 1558. In the final considerations, we will identify what were the present conditions in the missionary experience that led Nóbrega to announce a new strategy for the conversion of the indigenous people in 1558.